A high temperature nylon composition and its preparation method and application

By adding bis(hexamethylene) triamine groups and low-melting glass powder to high-temperature nylon resin, adjusting the thermal decomposition temperature of the resin, the bubble and yellowing problems of high-temperature nylon materials during lead-free reflow soldering is solved. , reduces the amount of halogen-free flame retardant, improves the flame retardant stability, and meets the flame retardant standards of V-1 or above.

CN116769305BActive Publication Date: 2025-02-11ZHUHAI WANTONG SPECIAL ENG PLASTICS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210225358.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-09
Publication Date
2025-02-11
Estimated Expiration
2042-03-09

AI Technical Summary

Technical Problem

The existing high-temperature nylon materials have problems of bubbles and yellowing during lead-free reflow soldering, and the halogen-free flame retardant used is large in addition, resulting in high cost and reduced material performance.

Method used

By adding 0.3-1.1% by weight of bis(hexamethylene) triamine groups to the high-temperature nylon resin and adding 1-5 parts of low-melting glass powder, the thermal decomposition temperature of the resin and the melt sintering of the glass powder are adjusted. The temperature matches it with the decomposition temperature of the flame retardant, promotes the formation of the carbon layer and improves the flame retardant stability.

Benefits of technology

It significantly improves the bubble and yellowing problems of high-temperature nylon materials during lead-free reflow soldering, reduces the amount of diethyl aluminum hypophosphate, improves the flame retardant stability, and meets the flame retardant standards above V-1. At the same time, the material's baking resistance is maintained.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-temperature nylon composition, which comprises the following components by weight: 100 parts of high-temperature nylon resin; 10-20 parts of diethyl aluminum hypophosphite; 1-5 parts of glass powder; the high-temperature nylon resin contains 0.3-1.1wt% of bis(hexamethylene)triamine groups; the melting point range of the glass powder is 420-500°C. The invention can significantly solve the defects of easy foaming and yellowing of flame-retardant high-temperature nylon by adding glass powder with a specific melting point to the flame-retardant high-temperature nylon system and exploring the relationship between the melting point of the glass powder and the decomposition temperature of the high-temperature nylon resin and the decomposition temperature of the flame retardant, and the flame retardancy reaches V-1 and above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a high-temperature nylon composition and a preparation method and application thereof. Background Art

[0002] In recent years, with the requirements of high-density and high-precision assembly of electronic and electrical equipment, lead-free reflow soldering (SMT) has become the mainstream of assembly technology. However, the temperature of lead-free reflow soldering is relatively high, and the parts need to be exposed to 250-280℃ for a long time. Therefore, the resin materials used in lead-free reflow soldering must have excellent heat resistance to meet the use requirements, and high-temperature nylon materials have become the mainstream.

[0003] For a series of electronic and electrical parts such as TYPE-C, DDR, USB, etc., the country and the industry have clear flame retardant requirements, especially the environmental protection requirements in the past two years. Halogen-free flame retardant semi-aromatic nylon has become the mainstream demand in the industry. However, due to the high melting point of semi-aromatic nylon, almost all halogen-free flame retardants cannot be used in the system, otherwise, due to stability problems, foaming and serious gas will occur. At present, the halogen-free flame retardants used in the industry are all diethyl aluminum hypophosphite. However, diethyl aluminum hypophosphite has a relatively low flame retardant efficiency in semi-aromatic nylon, resulting in a relatively large addition amount. It is necessary to add 18%~20% to achieve a vertical combustion V-0 of about 0.8mm. At the same time, there is a certain volatility and it is not stable enough. Due to the high cost of diethyl aluminum hypophosphite (AlPi), the large amount of diethyl aluminum hypophosphite added greatly increases the cost, and also brings a series of problems such as poor mechanical properties, fluidity and color change; high diethyl aluminum hypophosphite addition also brings a series of problems such as mold corrosion and mold scale precipitation, and the actual use experience is extremely poor.

[0004] Therefore, people have been committed to finding flame retardant synergists to reduce the amount of diethyl aluminum hypophosphite. However, in the field of semi-aromatic nylon, there are always few synergists that can be selected in the field of halogen-free flame retardancy. Many synergists used on PA66 cannot be used on high-temperature nylon due to thermal stability. Patent CN105968804A uses modified montmorillonite as a synergist, but it also brings obvious color degradation problems. The material is obviously yellow and cannot be used as natural color materials and color matching products. CN102464881A uses boehmite as a synergist, but boehmite itself has too much damage to the deflection and toughness of the material. At the same time, the characteristic of boehmite releasing water at high temperature also affects the repeated use of recycled materials. Summary of the invention

[0005] The object of the present invention is to provide a high temperature nylon composition which has the advantage of not turning yellow and significantly improves the defect of blistering under lead-free reflow soldering.

[0006] Another object of the present invention is to provide a preparation method and application of the high temperature nylon composition.

[0007] The present invention is achieved through the following technical solutions:

[0008] A high temperature nylon composition, comprising the following components in parts by weight:

[0009] 100 parts of high temperature nylon resin;

[0010] 10-20 parts of diethyl aluminum hypophosphite;

[0011] 1-5 parts of glass powder;

[0012] The high temperature nylon resin contains 0.3-1.1wt% of bis(hexamethylene)triamine groups; and the initial melting point of the glass powder is in the range of 420-500°C.

[0013] The initial decomposition temperature range of the high-temperature nylon resin is 400-450°C.

[0014] The high temperature nylon resin is selected from at least one of PA10T and PA6T.

[0015] Preferably, the high temperature nylon resin contains 0.5-0.8wt% of bis(hexamethylene)triamine groups. As the content of bis(hexamethylene)triamine groups in the high temperature nylon resin increases, the foaming resistance increases, but the baking discoloration resistance decreases. Therefore, within the preferred range, the foaming resistance and baking discoloration resistance are well balanced.

[0016] Preferably, the initial decomposition temperature of the diethyl aluminum hypophosphite is in the range of 390-450° C. In the preferred decomposition temperature range of diethyl aluminum hypophosphite, the foaming resistance and baking discoloration resistance are the best.

[0017] Preferably, the flame retardancy is best when the absolute value of the difference between the initial decomposition temperature of the high-temperature nylon resin and the initial decomposition temperature of diethyl aluminum hypophosphite is less than or equal to 30°C, and the absolute value of the difference between the initial decomposition temperature of the high-temperature nylon resin and the initial melting point of the glass powder is less than or equal to 35°C.

[0018] The initial decomposition temperature generally refers to the temperature corresponding to a weight loss of about 1% to 3%.

[0019] Whether to add 0-1 part of antioxidant can be decided according to actual needs.

[0020] The antioxidant may be: 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene; 2,5-di-tert-butyl-4-hydroxybenzyl dimethylamine; diethyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate; stearyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate; 3,5-di-tert-butyl-4-hydroxyphenyl-3,5-distearyl-thiotriazolylamine; 2,6-di-tert-butyl-4-hydroxymethylphenol; 2,4-di-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylglycerol allyl ether)-1,3,5-triazine; N,N'-hexamethylenediamine; (3,5-di-tert-butyl-4-hydroxy-hydrocinnamic acid); N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine; octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate; pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]; triethylene glycol-bis[3-(3,5-dimethyl-4-hydroxyphenyl) propionate]; triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate]; 2,2'-thiodiethyl-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, etc.

[0021] The preparation method of the high-temperature nylon composition of the present invention comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder, wherein the screw temperature ranges from 260 to 330° C. and the rotation speed ranges from 100 to 500 rpm to obtain the high-temperature nylon composition.

[0022] The high temperature nylon composition of the present invention is used for preparing electronic and electrical parts, specifically TYPC-C parts, USB parts, HDMI parts, etc.

[0023] The present invention has the following beneficial effects

[0024] The present invention controls the content of bis(hexamethylene)triamine in a high-temperature nylon composition to control the range of its thermal decomposition temperature, and further selects low-melting-point glass powders with different melting points, so that the melting and sintering temperature of the low-melting-point glass powder matches the decomposition temperature of the high-temperature nylon resin and the flame retardant, and the two interact with each other to accelerate the formation of a carbon layer, significantly improve the quality of the carbon layer, thereby improving the flame retardant stability, reducing the addition amount of the diethyl aluminum hypophosphite flame retardant, so that the flame retardant meets V-1 or above (0.8 mm), and the blistering after SMT reflow soldering and the baking yellowing resistance are significantly improved. DETAILED DESCRIPTION

[0025] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0026] The raw materials used in the embodiments and comparative examples are as follows:

[0027] The preparation method of high temperature nylon comprises the following steps:

[0028] According to the ratio, decanediamine, terephthalic acid, benzoic acid end-capping agent, bis(hexamethylene)triamine and deionized water are added into a reactor with nitrogen atmosphere and pressure of 2.8 MPa. The reactor is heated to 180°C and kept at this temperature for 0.5-1.5 hours, then heated to 235°C and kept at this temperature for 10-15 hours to obtain PA10T.

[0029] According to the ratio, hexamethylenediamine, terephthalic acid, benzoic acid end-capping agent, bis(hexamethylene)triamine and deionized water are added into a reactor with nitrogen atmosphere and pressure of 2.8 MPa. The reactor is heated to 180°C and kept at this temperature for 0.5-1.5 hours, then heated to 235°C and kept at this temperature for 10-15 hours to obtain PA6T.

[0030] The present invention can adjust the cross-linking structure of the resin by controlling the addition amount of bis(hexamethylene)triamine, thereby controlling the decomposition temperature thereof. The more the triamine is added, the more network structures of the cross-linking process of the resin are, and the higher the decomposition degree is.

[0031] PA10T-A: initial decomposition temperature 400°C, self-made, bis(hexamethylene)triamine addition amount 0.3wt% (based on the total monomer addition amount);

[0032] PA10T-B: initial decomposition temperature 415°C, self-made, bis(hexamethylene)triamine addition amount 0.5wt% (based on the total monomer addition amount);

[0033] PA10T-C: initial decomposition temperature 430°C, self-made, bis(hexamethylene)triamine addition amount 0.8wt% (based on the total monomer addition amount);

[0034] PA10T-D: initial decomposition temperature 450°C, homemade, 1.1wt% bis(hexamethylene)triamine addition (based on the total monomer addition);

[0035] PA10T-E: initial decomposition temperature 370°C, self-made, 0wt% bis(hexamethylene)triamine addition (based on the total monomer addition);

[0036] PA10T-F: initial decomposition temperature 380°C, self-made, bis(hexamethylene)triamine addition amount 0.15wt% (based on the total monomer addition amount);

[0037] PA10T-G: initial decomposition temperature 460°C, self-made, bis(hexamethylene)triamine addition amount 1.2wt% (based on the total monomer addition amount);

[0038] PA6T: initial decomposition temperature 405°C, homemade, bis(hexamethylene)triamine addition amount 0.7wt% (based on the total monomer addition amount);

[0039] Diethylaluminum hypophosphite A: initial decomposition temperature 380°C, brand ADP-30, manufacturer Oupure;

[0040] Diethylaluminum hypophosphite B: initial decomposition temperature 390°C, brand 8003, manufacturer Liside;

[0041] Diethylaluminum hypophosphite C: initial decomposition temperature 400°C, brand OP1230, manufacturer Clariant Chemicals;

[0042] Glass powder A: melting range 420-450℃ (initial melting point 420℃), brand V200, manufacturer: British Paulam;

[0043] Glass powder B: melting range 450-500℃ (initial melting point 450℃), brand V300, manufacturer: British Paulam;

[0044] Glass powder C: melting range 540-570℃ (initial melting point 540℃), brand V300+, manufacturer: British Paulam.

[0045] Embodiment and comparative example The preparation method of the flame retardant high temperature nylon composition: according to the ratio, the components are mixed evenly, and granulated by extrusion through a twin-screw extruder, the screw temperature range is 260-330°C, and the rotation speed range is 100-500rpm to obtain a high temperature nylon composition.

[0046] Various test methods:

[0047] (1) Flame retardant: Referring to the UL94 V-0 test standard, the standard strip specimen size is 125±5mm in length, 13.0±0.5mm in width and 0.8mm in thickness; 5 specimens are treated at 23±2℃ and 50±5% humidity for at least 48 hours. Aim the flame of the Bunsen burner at the center of the lower end of the specimen, and keep the distance between the center of the top surface of the Bunsen burner tube and the lower end surface of the specimen at 10±1mm, and maintain this distance for 10±0.5S: if necessary, the Bunsen burner can be moved as the length and position of the specimen change. After applying the flame to the specimen for 10±0.5S, immediately withdraw the Bunsen burner at a speed of about 300mm / s to at least 150mm away from the specimen. At the same time, use a timing device to measure the flame burning time T1 (in seconds) of the specimen. After the burning of the sample stops, even if the Bunsen burner is not evacuated 150mm away from the sample, immediately move the Bunsen burner to the lower end of the sample and keep a distance of 10±1mm, and ignite the flame again for 10±0.5S. If necessary, move the Bunsen burner away to clear the dripping. After igniting the flame, immediately move the Bunsen burner away from the sample by at least 150mm. At the same time, start the timing device to measure the flame time T2 and the flameless burning time T3 of the sample, and record T2 and T3. If T1+T2+T3 of all 5 specimens is less than 10s, and there is no dripping to ignite the cotton below, it is considered that the V-0 condition is met.

[0048] (2) Test for color change resistance during baking: Heat and melt the halogen-free flame-retardant high-temperature nylon composite material at 290-330°C, and then perform injection molding to make a 60mm*60mm*1mm square plate. Then, place the plate through an oven at a temperature of 240-260-280-300°C and a speed of 480mm / min for 7 minutes and 30 seconds. The LAB value change △E of the square plate before and after the test is recorded to measure the color change resistance during baking.

[0049] (3) Foaming test: The halogen-free flame-retardant high-temperature nylon composite material was heated and melted at 290-330°C, and injection molded to make a 60mm*60mm*1mm square plate. The plate was modulated at 85°C / 85% humidity for 168 hours, and then SMT tested at a temperature of 240°C-260°C-280°C-300°C to observe its foaming properties (100 plates were processed and the total number of square plates with foaming was counted).

[0050] Table 1: Contents (parts by weight) of various components of high temperature nylon compositions of Examples 1-7 and test results

[0051] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 PA10T-A 100 PA10T-B 100 PA10T-C 100 100 100 PA10T-D 100 PA6T 100 Diethylaluminum hypophosphite C 15 15 15 15 15 10 20 Glass powder B 2 2 2 2 2 5 1 Flame retardant V-1 V-0 V-0 V-1 V-1 V-0 V-0 △E 8.0 8.3 8.5 10.2 8.4 7.7 10.2 Foaming, block 10 2 0 0 0 0 12

[0052] It can be seen from Examples 1-5 and Examples 8-12 that when the content of bis(hexamethylene)triamine groups in the high temperature nylon resin is between 0.5-0.8 wt %, ΔE and foaming properties are well balanced.

[0053] It can be seen from Examples 3 / 6 / 7 and Comparative Example 5 that glass powder can effectively reduce the amount of diethylaluminum hypophosphite added, thereby improving the resistance to blistering and resistance to baking discoloration.

[0054] Table 2: Content of each component (parts by weight) and test results of high temperature nylon compositions of Examples 8-12

[0055] Example 8 Example 9 Example 10 Embodiment 11 Example 12 PA10T-A 100 PA10T-B 100 PA10T-C 100 PA10T-D 100 PA6T 100 Diethylaluminum hypophosphite B 15 15 15 15 15 Glass powder A 2 2 2 2 2 Flame retardant V-0 V-0 V-1 V-1 V-0 △E 8.5 8.8 9.1 10.4 9.0 Foaming, block 12 3 0 0 0

[0056] It can be seen from Examples 1-5 and Examples 8-12 that the flame retardancy is best when the absolute value of the difference between the decomposition temperature of the high-temperature nylon resin and the initial decomposition temperature of diethylaluminum hypophosphite is less than or equal to 30°C, and the absolute value of the difference between the initial decomposition temperature of the high-temperature nylon resin and the initial melting point of the glass powder is less than or equal to 35°C.

[0057] Table 2: Contents (parts by weight) of each component in Example 13 and the comparative example high temperature nylon composition and test results

[0058] Embodiment 13 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 PA10T-C 100 100 100 100 PA10T-E 100 PA10T-F 100 PA10T-G 100 Diethylaluminum hypophosphite A 15 23 Diethylaluminum hypophosphite C 15 15 15 15 23 Glass powder A 2 2 2 2 Glass powder C 2 Flame retardant V-1 V-1 V-1 V-2 V-2 V-0 V-0 △E 9.8 8.0 8.3 14.7 8.8 13.1 14.3 Foaming, block 6 58 44 0 0 81 100

[0059] It can be seen from Example 10 / 13 that the initial decomposition temperature of diethylaluminum hypophosphite is lower than 390°C, which easily causes blistering and yellowing.

[0060] It can be seen from Comparative Examples 1-3 that, on the one hand, when the content of bis(hexamethylene)triamine groups in the high-temperature nylon resin is not within the scope of the present invention, a good balance between ΔE and foaming properties cannot be obtained at the same time; on the other hand, since the content of bis(hexamethylene)triamine groups affects the decomposition temperature of the resin, it will also affect the flame retardancy of the formulation.

[0061] It can be seen from Comparative Example 4 that the initial melting point of the glass powder is too high, which will lead to a decrease in flame retardancy.

[0062] It can be seen from Comparative Examples 5-6 that the addition of glass powder can effectively reduce the addition amount of diethylaluminum hypophosphite, thereby improving the high temperature yellowing resistance and foaming properties.

Claims

1. A high temperature nylon composition, characterized in that: By weight, it includes the following components: 100 parts of high temperature nylon resin; 10-20 parts of diethyl aluminum hypophosphite; 1-5 parts of glass powder; The high temperature nylon resin contains 0.3-1.1wt% of bis(hexamethylene)triamine groups; The initial melting point range of the glass powder is 420-500 ℃; The initial decomposition temperature range of the high temperature nylon resin is 400 ~ 450 ℃; The initial decomposition temperature of the diethyl aluminum hypophosphite is in the range of 390-450°C; The high temperature nylon resin is selected from at least one of PA10T and PA6T.

2. The high temperature nylon composition according to claim 1, characterized in that: The high temperature nylon resin contains 0.5-0.8wt% of bis(hexamethylene)triamine groups.

3. The high temperature nylon composition according to claim 1, characterized in that: The absolute value of the difference between the initial decomposition temperature of the high temperature nylon resin and the initial decomposition temperature of diethylaluminum hypophosphite is less than or equal to 30°C, and the absolute value of the difference between the initial decomposition temperature of the high temperature nylon resin and the initial melting point of the glass powder is less than or equal to 35°C.

4. The high temperature nylon composition according to claim 1, characterized in that: By weight, 0-1 part of antioxidant is also included.

5. The method for preparing the high temperature nylon composition according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating the components through a twin-screw extruder, wherein the screw temperature ranges from 260 to 330° C. and the rotation speed ranges from 100 to 500 rpm to obtain a high-temperature nylon composition.

6. Use of the high temperature nylon composition according to any one of claims 1 to 4, characterized in that: Used to prepare electronic and electrical parts.

Citation Information

Patent Citations

  • Halogen-free flame-retardant polyamide composition

    CN102464881A

  • Flame-retardant and high-temperature-resistant nylon composite material and preparation method thereof

    CN105968804A

  • Flame-retardant halogen-free flame-retardant reinforced nylon composite material

    CN111793358A

  • Star-and tree-shaped branched polymers having flame-retardant properties

    US20130281654A1